Comportamiento y variación del riesgo psicosocial en el ámbito laboral y patológico en el personal de un distrito de salud de Cotacachi - Mena Maldonado, Sofía Carolina (2023)
The study focuses on the factors associated with psychosocial risk, which are factors that affect the health of the individual in the work area or organization and that result in physiological, emotional, cognitive and behavioral responses, the same ones that can be potentially precursors for the development of pathologies according to the intensity, frequency and duration of the risk factor. The purpose of the research was to determine the behavior and variation of psychosocial risk in the workplace and pathology in the personnel of a Cotacachi Health District. A quantitative and cross-sectional investigation was carried out, having as a sample 328 collaborators from a health district of Cotacachi, to whom the psychosocial risk assessment instrument proposed by the Ministry of Labor was applied. Among the main results obtained, it is observed that there is a low risk corresponding to 49.09% of the collaborators, followed by 46.95% of collaborators with medium risk and to a lesser extent 3.96% with high risk of Psychosocial risk. Therefore, it is considered conclusive to design an epidemiological surveillance plan (EVP) aimed at preventing this type of factor to improve the work environment in the short and medium term.